1989
DOI: 10.1084/jem.170.4.1457
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of a cDNA expressing a recombinant house dust mite protein that binds human IgE and corresponds to an important low molecular weight allergen.

Abstract: A cDNA clone coding for a mite allergen of mol wt approximately 14,000 has been isolated and its DNA sequence determined. The native component from mite extracts encoded by this DNA was identified by immunoprobing blots of mite body extract with human IgE eluted from the electroblotted cloned fusion polypeptides derived from the expressed cDNA clone. The clone encodes a polypeptide with a deduced mol wt of 17,460. The deduced amino acid sequence was not homologous to any known protein sequences and it contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 8 publications
1
42
0
2
Order By: Relevance
“…Both the cross–reactivity between BtM and Der p 5 and the coexistence of the two mite species in the region can explain the significant correlation observed between RAST values of sera reacting with the two mite extracts and the recombinants. It has been shown that BtM and Der p 5 have equivalent native allergens in whole mite extracts [11, 22]. We now describe that these allergens account for almost 25% of the IgE antibody binding capacity of their mite extracts.…”
Section: Discussionmentioning
confidence: 92%
“…Both the cross–reactivity between BtM and Der p 5 and the coexistence of the two mite species in the region can explain the significant correlation observed between RAST values of sera reacting with the two mite extracts and the recombinants. It has been shown that BtM and Der p 5 have equivalent native allergens in whole mite extracts [11, 22]. We now describe that these allergens account for almost 25% of the IgE antibody binding capacity of their mite extracts.…”
Section: Discussionmentioning
confidence: 92%
“…Subsequent studies with Der p 4 affinity purified with cyclodextrin showed 80% binding but the binding was extremely low and IgE from less than 40% of subjects bound IgE at >2 ng/ml [36]. The group 5 and 7 allergens react with IgE in 50% of sera often with a magnitude as high as the major allergens [37, 38, 39]. Der p 8 has been reported to bind IgE in 50% of sera from allergic subjects but quantitative studies have not been performed [40].…”
Section: Ige Binding To Purified Allergensmentioning
confidence: 99%
“…Der p 5 was identified from a partial cDNA clone which produced a polypeptide reactive with IgE in 40% of allergic sera [39]. The sequence encoded a 17,000 MW polypeptide with no N-glycosylation sites or cysteines, but IgE antibody affinity purified from the recombinant protein reacted with a 14,000 MW band in mite extracts.…”
Section: Group 5 Allergensmentioning
confidence: 99%
“…Allergens do not seem to have specific biological functions explaining their allergenicity, but it is demonstrated more and more that biological activity of allergens may promote the immunological conditions necessary for specific sensitization towards allergens. The best–analyzed example in this context is Der p 1, the major allergen of mites known to be a cysteine protease [17]. It was shown to augment its own permeability in the bronchial epithelium by proteolytic activity [29].…”
Section: Influence Of Functional Properties Of Allergensmentioning
confidence: 99%